Ubiquitin-proteasomal regulation of chromatin remodeler INO80 in the nucleus accumbens mediates persistent cocaine craving - Werner, C. T. (Sci Adv, 2019)
Neuroadaptations in the nucleus accumbens (NAc) underlie cue-induced cocaine craving that intensifies (“incubates”) during abstinence and is believed to contribute to persistent relapse vulnerability. Changes in gene expression often govern perpetual behavioral abnormalities, but epigenetic plasticity during prolonged abstinence from drug exposure is poorly understood. We examined how E3 ubiquitin ligase TRIM3 dysregulates chromatin remodeler INO80 to mediate cocaine craving during prolonged abstinence. We found that INO80 expression increased in the NAc on abstinence day 30 (AD30) but not on AD1 following cocaine self-administration. Furthermore, TRIM3, which mediates degradation of INO80, was reduced on AD30, along with TRIM3-INO80 interaction. Viral-mediated gene transfer of INO80 or TRIM3 governed cocaine craving during prolonged abstinence. Lastly, chromatin immunoprecipitation followed by massively parallel DNA sequencing identified INO80-mediated transcriptional regulation of predicted pathways associated with cocaine plasticity. Together, these results demonstrate a novel ubiquitin-proteasomal-epigenetic mechanism by which TRIM3-INO80 mediates cocaine craving during prolonged abstinence.